Studi Evaluasi Program Kampus Mengajar Melalui Pendekatan Kirkpatrick Dari Sudut Pandang Dosen Pembimbing Lapangan - Endi Rochaendi; Nur Kholik; Indah Perdana Sari; Dyahsih Alin Sholihah; Mahfud Mahfud; Saepul Ma'mun (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The study in this research describes and evaluates the implementation of the Teaching Campus Program (PKM) from the perspective of Field Supervisors (DPL). The research aims to determine the extent of success in implementing PKM using the Kirkpatrick model approach via reaction level, learning level, behaviour level and result level. The research method used is a qualitative study approach, with the type of research being desk study. The results of research based on the DPL perspective, the implementation of PKM has produced positive reactions to empower attitudes, knowledge and skills, enrich insight and knowledge in student mastery, educational learning and science and the teaching field, explore creativity and development of thought patterns, attitude patterns and action patterns. Integrating PKM participants and the emergence of orientation, adaptation, observation and implementation treatment from participants towards PKM activities. It was concluded that PKM had increased the basic competencies, supporting competencies and special competencies of PKM participants. To increase the level and weight of PKM, it is necessary to utilize a pedagogical flexibility framework so that in completing the objectives of PKM, it becomes more operational, and the impact it will produce is visible.